2006
DOI: 10.1139/l06-013
|View full text |Cite
|
Sign up to set email alerts
|

Macro-level collision prediction models for evaluating neighbourhood traffic safety

Abstract: This study describes the development of macro-level (i.e., neighbourhood or traffic zone level) collision prediction models using data from 577 neighbourhoods across the Greater Vancouver Regional District. The objective is to provide a safety planning decision-support tool that facilitates a proactive approach to community planning which addresses road safety before problems emerge. The models are developed using the generalized linear regression modelling (GLM) technique assuming a negative binomial error st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(55 citation statements)
references
References 7 publications
3
48
0
4
Order By: Relevance
“…The literature is replete with studies showing that areas with more residents, more employment and more arterial lane miles experience more crashes (Hadayeghi et al, 2003(Hadayeghi et al, , 2006Kmet et al, 2003;Ladro´n de Guevara et al, 2004;Levine et al, 1995aLevine et al, , 1995bLovegrove and Sayed, 2006). Such studies may be useful for crash prediction on individual facilities.…”
Section: Crash Risk Factorsmentioning
confidence: 99%
“…The literature is replete with studies showing that areas with more residents, more employment and more arterial lane miles experience more crashes (Hadayeghi et al, 2003(Hadayeghi et al, , 2006Kmet et al, 2003;Ladro´n de Guevara et al, 2004;Levine et al, 1995aLevine et al, , 1995bLovegrove and Sayed, 2006). Such studies may be useful for crash prediction on individual facilities.…”
Section: Crash Risk Factorsmentioning
confidence: 99%
“…This very important additional attribute of these models provides some extra information as it takes the spatial location of a crash into consideration. Lovegrove and Sayed (2006) concluded that quantifying the relationship between the zonal characteristics such as exposure, network, socio-demographic and TDM variables and crashes at a zonal level provides a predictive tool to predict the NOCs in a TAZ. They used GLM techniques to develop ZCPMs for both urban and rural areas across the Greater Vancouver Regional District (GVRD).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, recent area-level studies have reported that traffic volume and urban arterial roads are independently associated with a greater incidence of road injuries within neighbourhoods. 3,8,9 In Montréal, the presence of arterial roads at intersections significantly increases the number of injured pedestrians, cyclists and motor-vehicle occupants, even when other intersection characteristics are taken into account. 10 By definition, an urban arterial road has more traffic lanes and is consequently wider, has higher average vehicle speeds and longer emergency stopping distances.…”
mentioning
confidence: 99%